PENINGKATAN HASIL BELAJAR IPA PESERTA DIDIK KELAS IX- 4 MELALUI METODE DISKUSI KELOMPOK KECIL (BUZZ GROUP DISCUSSION) DI SMP NEGERI 7 MATARAM - MISKAH MISKAH (GANEC SWARA, 2018)
This Classroom Action Research (CAR) was conducted at SMP 7 Mataram with the aim of improving science learning outcomes, through small group discussion methods (Buzz Group Discussion). The type of research used is Classroom Action Research which consists of planning, implementing, observing, and reflecting. The research subjects were 44 students of class IX-4 Mataram 7 SMP. This CAR is carried out in two cycles, where each cycle consists of 2 meetings. The action in this study was the use of group discussion methods (Buzz Group Discussion). Data on student learning outcomes are obtained from the test results at the end of each lesson, while teacher activity data is collected by observation through observation sheets at each meeting. Furthermore, the collected data were analyzed using qualitative descriptive.From the results of the study found that the average value of learning outcomes of students from cycle I to cycle II has increased from 70.93 to 80.36, while for completeness in the first cycle the number of students who complete as many as 29 people (65.91%), and II to 40 people (90.91%). So there is an increase from cycle I to cycle II by 25% for completeness of learning. Thus it can be concluded that the use of small group discussion methods (Buzz Group Discussion) can improve student learning outcomes in science learning class IX-4 of SMP Negeri 7 Mataram